Habilidades sociais e comportamento do motorista entre universitárias usuárias e não usuárias de bebida alcoólica - Silva, Adilson Gonçalves da [UNESP] (2015)
Traffic accidents have a high incidence among young people, but can be prevented with traffic education, advocated for higher education. Studies that investigate variables associated with these accidents can promote curricular inclusion of the subject, especially in courses in the humanities and health. This descriptive study compares and investigates the relationship between social skills, behavior in traffic and alcohol in university, differentiated by type of college, course characteristics, involvement in traffic accidents and sociodemographic variables. Were applied in the classroom, three questionnaires (Questionnaire Driver-QCM Behavior Questionnaire Assessment of Social Skills - behaviors and contexts for University - QHC-University and Alcohol Use Disorders Identification Test - AUDIT) in 472 university students of the courses Speech Therapy and Pedagogy in two colleges, one public and other private. There were: superior means of error behaviors (17,00), lapses (21.20) and rape (22.39) among university that drank alcohol compared with those who did not (16.02 / 19, 24 / 19,66); highest average in social skills in alcohol users (2.24) compared to non-users (1.70) as the public speaking in students enrolled in community college (49.23) and pedagogy students (48, 67); superior means as the use of alcohol among students of Speech Therapy (4.99) in relation to Education (2.59); positive correlation between the use of alcohol with driver behavior (p≤0,000) and social skills related to public speaking (p≤0,027). It was concluded that the graduation students of the community college and the course of speech therapy are more alcohol and have more risky behavior in traffic. The survey results can be considered as indicators to enlarge the possibilities of self-protection and prevention of traffic accidents in the study population as well as composing educational actions to be inserted in curriculum in higher education, aimed to...